Desenvolvimento de um modelo numérico para a simulação da formação de hidratos em paredes de tubulações - Dextre, Gino Noel Delgado (2017)
Over the years, the formation of hydrates has been a constant challenge for the oil and gas industry. It has been sought to understand the different processes involved on hydrates formation, in that way, the development of semi-empirical models has been carried out. These models consider that main phenomenon is governed both heat and mass transfer and chemical kinetics. However, the lack of a model that relates these three effects represents a limitation in the understanding of the process of hydrate growth, mainly for systems where substances are in different states and / or compositions. Therefore, in the present work a mathematical model to predict the hydrate growth rate considering the relations between heat and mass transfer and chemical kinetics is proposed. In addition, a new approach is considered, in which is including hydrate porosity through a mathematical-numerical strategy implemented in the ANSYS / FLUENT software. The effects due to hydrate growth are considered by a growth rate coupled to the source terms of the constitutive equations of the problem. It is important to mention that the hydrate formation rate and the hydrate mass conservation equation were implemented via user defined functions (User Defined Functions). The proposed model was validated by comparing with the experimental results of THF hydrate formation diluted in a stoichiometric ratio of 1:17 in a cylindrical static cell. It is intended that the mathematical model proposed serves as a theoretical basis for future models for predicting formation and growth of hydrates in oil and gas transport pipes.